Medical cannabis treatment for chronic pain: Outcomes and prediction of response. (9th November 2020) - Aviram, Joshua; Pud, Dorit; Gershoni, Tamar; Schiff‐Keren, Bareket; Ogintz, Miriam; Vulfsons, Simon; Yashar, Tamar; Adahan, Haim‐Moshe; Brill, Silviu; Amital, Howard; Goor‐Aryeh, Itay; Robinson, Dror; et al.
Abstract: Background: Although studied in a few randomized controlled trials, the efficacy of medical cannabis (MC) for chronic pain remains controversial. Using an alternative approach, this multicentre, questionnaire‐based prospective cohort was aimed to assess the long‐term effects of MC on chronic pain of various aetiologies and to identify predictors for MC treatment success. Methods: Patients with chronic pain, licensed to use MC in Israel, reported weekly average pain intensity (primary outcome) and related symptoms before and at 1, 3, 6, 9 and 12 months following MC treatment initiation. A general linear model was used to assess outcomes and identify predictors for treatment success (≥30% reduction in pain intensity). Results: A total of 1, 045 patients completed the baseline questionnaires and initiated MC treatment, and 551 completed the 12‐month follow‐up. At 1 year, average pain intensity declined from baseline by 20% [−1.97 points (95%CI = −2.13 to −1.81; p < 0.001)]. All other parameters improved by 10%–30% ( p < 0.001). A significant decrease of 42% [reduction of 27 mg; (95%CI = −34.89 to 18.56, p < 0.001)] from baseline in morphine equivalent daily dosage of opioids was also observed. Reported adverse effects were common but mostly non‐serious. Presence of normal to long sleep duration, lower body mass index and lower depression score predicted relatively higher treatment success, whereas presence of neuropathic pain predicted the opposite. Conclusions: This prospective study provides further evidence for the effects of MC on chronic pain and related symptoms, demonstrating an overall mild‐to‐modest long‐term improvement of the tested measures and identifying possible predictors for treatment success.